Smart security understanding and contributing to the business : proven practices - Quilter, J. David (Security Executive Council risk management portfolio, 2015)
Smart Security: Understanding and Contributing to the Business is a video presentation. Length: 68 minutes. In Smart Security: Understanding and Contributing to the Business, presenter J. David Quilter demonstrates the benefits of how a fully integrated security program increases business profits and delivers smart security practices at the same time. The presentation does away with the misconception that security is only an expense. In fact, a well-integrated security program can protect business interests, thereby enhancing productivity and net income. Quilter covers cost analysis and secu